Prime Editing: Mechanistic Insights and DNA Repair Modulation - Astrid Mentani; Marcello Maresca; Anna Shiriaeva (Cells)
Prime editing is a genome editing technique that allows precise modifications of cellular DNA without relying on donor DNA templates. Recently, several different prime editor proteins have been published in the literature, relying on single- or double-strand breaks. When prime editing occurs, the DNA undergoes one of several DNA repair pathways, and these processes can be modulated with the use of inhibitors. Firstly, this review provides an overview of several DNA repair mechanisms and their modulation by known inhibitors. In addition, we summarize different published prime editors and provide a comprehensive overview of associated DNA repair mechanisms. Finally, we discuss the delivery and safety aspects of prime editing.